PENERAPAN METODE PENEMUAN TERBIMBING DALAM MENYELESAIKAN SOAL TRIGONOMETRI - Fatimah Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2014)
This article presents the use of guided discovery learning method in solving trigonometry. Guided discovery learning method can be used as an alternative that can be used by educators (teachers) as the first step in solving trigonometry problems. Guided discovery learning method that intended in this article is a way to convey ideas through the process of finding ideas. Learners find their own patterns and mathematical structures through a series of learning experiences.